The Hepatotoxic Effect of Sildenafil Citrate and Its Combination with Tramadol on Male Wistar Rats is Ameliorated with Vitamin E Supplementation - , J. N. Nwangwa; , A. L. Udefa; , P. M. Obi; , C. E. Obeten; , S. Okpa (Archives of Current Research International, 2019)
Aims: This study investigated the effect of vitamin E on serum liver enzymes and bilirubin concentrations in male Wistar rats treated with sildenafil citrate (SC) and a combination of SC and tramadol on the background that these drugs cause oxidative damage to the liver. Methods: Thirty male Wistar rats (180-200 g) were randomly divided into six groups (n=5) thus: control (0.2 ml vehicle – olive oil), SC-treated group (Sil) (10 mg/kg of SC), SC+tramadol-treated group (Sil+Tra) (10 mg/kg of SC and 20 mg/kg of tramadol), vitamin E-treated group (Vit E) (100mg/kg of vitamin E), SC+vitamin E-treated group (Sil+Vit E) (received SC and vitamin E) and SC+tramadol+vitamin E-treated group (Sil+Tra+Vit E) (received SC, tramadol and vitamin E). Drugs were administered orally once daily for four weeks after which blood samples were obtained and used to measure serum concentrations of liver enzymes (AST, ALT and ALP) and bilirubin. Results: Serum AST, ALT, ALP, total bilirubin (TB) and unconjugated bilirubin (UCB) concentrations were significantly (p<0.001) increased in Sil and Sil+Tra compared with control and Vit E and significantly (p<0.01) decreased in Sil+Vit E and Sil+Tra+Vit E compared with Sil and Sil+Tra. Serum conjugated bilirubin (CB) concentration and percentage conjugation of bilirubin significantly decreased (p<0.001) in Sil and Sil+Tra compared with control and Vit E and increased (p<0.01) in Sil+Vit E and Sil+Tra+Vit E compared with Sil and Sil+Tra. Conclusion: SC, administered separately and in combination with tramadol altered liver function. However, vitamin E supplementation was able to ameliorate this alteration in liver function.